Preparation method of ultralow-porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating
By combining microarc oxidation treatment and polycaprolactone coating on the surface of the magnesium alloy, an ultra-low porosity corrosion-resistant and wear-resistant coating is formed, which solves the problems of excessively fast degradation rate and poor corrosion resistance of the magnesium alloy, and improves the long-term corrosion resistance and wear resistance of the magnesium alloy.
Patent Information
- Application Number
- CN202411816729.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-25
AI Technical Summary
The degradation rate of magnesium alloys is too fast, resulting in adverse effects such as gas aggregation and local tissue alkalization in medical applications, and its poor corrosion resistance limits its widespread application.
The preparation method of microarc oxidation corrosion-resistant and wear-resistant coating of ultra-low porosity magnesium alloy is adopted, and a composite film layer with high corrosion resistance and wear resistance is formed by combining microarc oxidation treatment and polycaprolactone coating.
It significantly reduces the porosity and roughness of the surface coating of magnesium alloy, improves its long-term corrosion resistance and wear resistance, delays the degradation rate of magnesium alloy, and broadens its application range in harsh environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, and in particular relates to a method for preparing a micro-arc oxidation corrosion-resistant and wear-resistant coating of an ultra-low porosity magnesium alloy. Background Art
[0002] Magnesium is located in the second main group of the third period of the periodic table. Its unique hexagonal closest packing (hcp) gives it outstanding physical properties. It has a history of clinical application in the medical field for more than a hundred years, but its wide application is still limited. If the degradation rate of magnesium alloys is too fast, it may cause a series of adverse effects, such as local accumulation of gas and alkalization of local tissues. Therefore, improving the corrosion resistance of magnesium alloys is an urgent challenge to promote the medical application of magnesium alloys.
[0003] Micro-arc oxidation (MAO) is a surface modification technology that belongs to the category of electrochemical transfer. During the micro-arc oxidation process, valve metals such as aluminum, magnesium, titanium and their alloys are placed in a specific electrolyte. When the voltage reaches a certain value, plasma will be generated between the metal and the electrolyte interface. This process involves the interaction of thermochemistry, plasma chemistry and electrochemistry, causing the metal surface to undergo melting, eruption, crystallization and high-temperature phase change, and finally forming a porous film layer on the surface of the magnesium alloy. This film layer not only significantly enhances the corrosion resistance of the base material, but also gives it unique biocompatibility and functionality. Summary of the invention
[0004] In order to solve the problems of too fast degradation rate and poor long-term corrosion resistance of magnesium alloy, the present invention provides a method for preparing a micro-arc oxidation corrosion-resistant and wear-resistant coating of an ultra-low porosity magnesium alloy.
[0005] The method for preparing the micro-arc oxidation composite coating on the surface of a medical magnesium alloy provided by the present invention comprises the following steps:
[0006] Step 1: After the magnesium alloy sheet is cut by a wire cutting machine, surface impurities are removed by sandpaper polishing, and then it is further rinsed with alcohol and dried to obtain a magnesium alloy sample.
[0007] Step 2: Add sodium hexametaphosphate ((Na2PO3)6), potassium hydroxide, ammonium bifluoride (NH4HF2), propylene glycol, and calcium lactate into deionized water, and stir until the solution is clear and transparent to obtain an electrolyte.
[0008] Step 3: The magnesium alloy sample in step 1 is used as an anode and a graphite plate or a stainless steel plate is used as a cathode. Micro-arc oxidation treatment is performed in the electrolyte obtained in step 2. After the treatment, it is rinsed with deionized water and dried with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0009] Step 4: The coating surface of the magnesium alloy sample having the micro-arc oxidation coating in step 3 is uniformly covered with a layer of polycaprolactone coating by an immersion pulling method.
[0010] Furthermore, in the above step 1, the surface of the magnesium alloy is polished using water-abrasive sandpaper with increasing roughness in sequence until the surface of the magnesium alloy is smooth and flat.
[0011] Furthermore, in the above step 1, the rinsing and drying is rinsing with alcohol and blowing dry.
[0012] Furthermore, in the above step 2, the electrolyte contains 3-9 g / L (Na2PO3)6, 1-5 g / L potassium hydroxide, 1-3 g / L NH4HF2, 6-8 mL / L propylene glycol and 3-9 g / L calcium lactate.
[0013] Furthermore, in the above step 3, the conditions of the micro-arc oxidation treatment are: the micro-arc oxidation power supply adopts constant current control, the voltage is 300-600V, and the current density is 1-10A / dm 2 , frequency is 200~1000Hz, duty cycle is 30%~60%, and electrolyte temperature is lower than 40℃.
[0014] Furthermore, in the above step 3, the time of the micro-arc oxidation treatment is 10 to 45 minutes.
[0015] The beneficial effects of the present invention are as follows:
[0016] The improved micro-arc oxidation electrolyte of the present invention has a simple preparation process, significantly inhibits the generation of electric sparks during the micro-arc oxidation process, and effectively reduces the surface micropore diameter of the micro-arc oxidation coating. In addition, the presence of calcium lactate in the electrolyte adjusts the microstructure of the micro-arc oxidation coating, deposits a large number of particles in the pores of the surface coating, further reduces the porosity of the coating, and also reduces the roughness of the coating, greatly improving the long-term corrosion resistance of the magnesium alloy micro-arc oxidation coating. Polycaprolactone, as a polymer material, has a controllable degradation rate and good physical properties, which can further enhance the corrosion resistance and wear resistance of the film layer. By coating polycaprolactone after micro-arc oxidation pretreatment, the composite film layer formed can not only effectively block the corrosive medium in the external environment and reduce the degradation rate of the magnesium alloy, but also provide long-term protection, improve the long-term corrosion resistance of the magnesium alloy, thereby broadening the application range of magnesium alloys in harsh environments such as moisture, salt, acidity and oxidation. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0018] Example 1
[0019] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0020] Step 2: Add 3 g of sodium hexametaphosphate, 1 g of potassium hydroxide, 1 g of ammonium bifluoride, and 6 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 3 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0021] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 450V and the current density is 2A / dm 2 , frequency 500 Hz, duty cycle 60%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 30 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0022] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in a sol containing 5wt.% polycaprolactone (polycaprolactone is dissolved in dichloromethane), ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.731μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.89×10 -6 cm 3 / (N·m).
[0023] Example 2
[0024] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0025] Step 2: Add 4 g of sodium hexametaphosphate, 2 g of potassium hydroxide, 1 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 3 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0026] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 350V and the current density is 3A / dm 2 , frequency 400 Hz, duty cycle 40%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 30 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0027] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.662μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.63×10 -6 cm 3 / (N·m).
[0028] Example 3
[0029] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0030] Step 2: Add 3 g of sodium hexametaphosphate, 3 g of potassium hydroxide, 1 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 3 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0031] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 450V and the current density is 3A / dm 2 , frequency 300 Hz, duty cycle 40%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 20 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0032] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.443μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.77×10 -6 cm 3 / (N·m).
[0033] Example 4
[0034] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0035] Step 2: Add 3 g of sodium hexametaphosphate, 4 g of potassium hydroxide, 2 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 5 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0036] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 450V and the current density is 7A / dm 2 , frequency 500 Hz, duty cycle 40%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 30 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0037] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.224μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.57×10 -6 cm 3 / (N·m).
[0038] Example 5
[0039] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0040] Step 2: Add 5 g of sodium hexametaphosphate, 4 g of potassium hydroxide, 3 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 6 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0041] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 350V and the current density is 6A / dm 2 , frequency 450 Hz, duty cycle 60%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 30 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0042] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.772μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.54×10 -6 cm 3 / (N·m).
[0043] Example 6
[0044] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0045] Step 2: Add 6 g of sodium hexametaphosphate, 3.5 g of potassium hydroxide, 2 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 6 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0046] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 350V and the current density is 2A / dm 2 , frequency 400 Hz, duty cycle 60%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 30 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0047] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.772μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.54×10 -6 cm 3 / (N·m).
[0048] Example 7
[0049] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0050] Step 2: Add 3 g of sodium hexametaphosphate, 3 g of potassium hydroxide, 1 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 3 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0051] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 350V and the current density is 4A / dm 2 , frequency 500 Hz, duty cycle 60%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 30 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0052] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.832μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.89×10 -6 cm 3 / (N·m).
[0053] Example 8
[0054] Step 1: Cut the magnesium alloy sheet into samples of 20mm×20mm×5mm with a wire cutting machine, and polish the sample surface with 240#, 400#, 600#, 800#, 1000#, and 2000# abrasive papers in turn until the surface of the magnesium alloy substrate is smooth and flat, then rinse with alcohol and blow dry to obtain a magnesium alloy sample.
[0055] Step 2: Add 3 g of sodium hexametaphosphate, 3 g of potassium hydroxide, 1 g of ammonium bifluoride, and 7 mL of propylene glycol to 500 mL of deionized water, and shake thoroughly with an ultrasonic oscillator to ensure that the substances are completely dissolved. Then add 3 g of calcium lactate and stir until the solution is clear and transparent. Then add deionized water until it reaches 1 L to obtain an electrolyte.
[0056] Step 3: The magnesium alloy sample in step 1 is used as the anode and the graphite plate is used as the cathode. The electrolyte obtained in step 2 is poured into the electrolytic cell. The micro-arc oxidation power supply adopts constant current control, and the power supply voltage is set to 400V and the current density is 2A / dm 2 , frequency 400 Hz, duty cycle 50%, electrolyte temperature below 40°C, micro-arc oxidation treatment for 40 minutes, after treatment, rinse with deionized water and dry with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating.
[0057] Step 4: Connect and fix the magnesium alloy sample with micro-arc oxidation coating on the wire, install it on the pulling machine, immerse the sample vertically in the sol containing 5wt.% polycaprolactone, ensure that the sample is completely immersed, and stay for 10 minutes to allow the sol to fully penetrate into the pores on the surface of the sample, and then pull the sample out of the sol vertically at a constant speed of 1cm / min to ensure that a uniform and continuous film is formed on the surface of the sample. After pulling, let it stand for 10 minutes so that the sol attached to the surface of the sample will gradually gel. The roughness of the sample was tested using the SJ-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the roughness was 1.665μm. The wear rate of the sample was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. and was 1.45×10 -6 cm 3 / (N·m).
Claims
1. A method for preparing an ultra-low porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating, characterized in that: The preparation method comprises the following steps: Step 1: cutting, grinding, rinsing and drying the magnesium alloy to obtain a magnesium alloy sample; Step 2: Add sodium hexametaphosphate, potassium hydroxide, ammonium bifluoride, glycerol, and calcium lactate into deionized water, and stir until the solution is clear and transparent to obtain an electrolyte; Step 3: The magnesium alloy sample in step 1 is used as an anode, and the graphite plate or the stainless steel plate is used as a cathode, and a micro-arc oxidation treatment is performed in the electrolyte obtained in step 2, and after the treatment, it is rinsed with deionized water and dried with hot air to obtain a magnesium alloy sample with a micro-arc oxidation coating; Step 4: The coating surface of the magnesium alloy sample having the micro-arc oxidation coating in step 3 is uniformly covered with a layer of polycaprolactone coating by an immersion pulling method.
2. The method for preparing the ultra-low porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating according to claim 1, characterized in that: In step 1, the surface of the magnesium alloy is polished using water-abrasive sandpaper with increasing roughness until the surface of the magnesium alloy is smooth and flat, and then rinsed with alcohol and blown dry.
3. The method for preparing the ultra-low porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating according to claim 1, characterized in that: In step 2, the electrolyte contains 3-9 g / L sodium hexametaphosphate, 1-5 g / L potassium hydroxide, 1-3 g / L ammonium bifluoride, 6-8 mL / L propylene glycol and 3-9 g / L calcium lactate.
4. The method for preparing the ultra-low porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating according to claim 1, characterized in that: In step 3, the conditions of the micro-arc oxidation treatment are: the micro-arc oxidation power supply adopts constant current control, the voltage is 300-600V, and the current density is 1-10A / dm 2 , frequency is 200~1000Hz, duty cycle is 30%~60%, and electrolyte temperature is lower than 40℃.
5. The method for preparing the ultra-low porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating according to claim 1 or 4, characterized in that: In step 3, the micro-arc oxidation treatment time is 10 to 45 minutes.